Relationship Between Toxoplasma gondii and Mood Disturbance in Women Veterans. Issue 6 (1st June 2015) - Duffy, Allyson R.; Beckie, Theresa M.; Brenner, Lisa A.; Beckstead, Jason W.; Seyfang, Andreas; Postolache, Teodor T.; Groer, Maureen W.
ABSTRACT: Background: Toxoplasma gondii is an intracellular protozoan parasite with zoonotic potential that causes acute and chronic diseases, which has been associated with schizophrenia, depression, bipolar disorder, and suicidal behavior. Military personnel may be at increased risk for exposure to the parasite when deployed to countries with high prevalence rates. Methods: Women Veterans were recruited to participate in the study at an event to recognize women Veterans and later through e-mails. Blood samples were collected from 70 women Veterans (mean age: 47 years) and analyzed for T. gondii IgG titer. Participants completed a demographic instrument, Center for Epidemiologic Studies Depression scale, Profile of Mood States (POMS), and Post-Traumatic Stress Disorder Checklist-Military. Results: The infectivity rate was lower than the rate in the United States (11.4% [8 out of 70 were seropositive], but 6 of the 8 [75%] had been deployed outside the United States. Pearson correlations and t tests showed significant relationships between T. gondii seropositivity and Center for Epidemiologic Studies Depression score), POMS-depression, POMS-confusion, and POMS-anger subscale scores, and total mood disturbance score. Conclusions: This study is the first to describe biobehavioral relationships between chronic T. gondii infection, depression, and dysphoric moods in a military veteran population.